A non-operative management of chronic anal fissure. - Azhar Shah (Gandhara University, 2018)
OBJECTIVES Assessment of efficacy of topical 0.2% glyceryl trinitrate ointment in the treatment of chronic anal fissure. PATIENTS AND METHODS A prospective study was carried out at surgical outpatient department Town Teaching Hospital from January 2017 to July 2017. Fifty consecutive patients were treated with 0.2% glyceryl trinitrate ointment and reviewed at 3, 6 and 12 weeks interval. Data was collected on a designed questionnaire. RESULT At six weeks fissure healed in 70% patients. There was significant reduction in the symptoms of pain, bleeding and irritation. 30% Patient treated was not successful. At 03 months interval there was no recurrence with 70% healing rate. Patients whose fissure healed reported an improvement in bodily pain, health perception, vitality and mental health. CONCLUSION The use of topical 0.2% glyceryl trinitrate has proved to be as effective option in managing chronic anal fissure with 70% healing rate in this study bearable side effect and it leads to improvement in health related quality of life.